"Il magnifico sforzo". Modernizzazione, ingegnerizzazione e disciplinarmente infrastrutturale dei cinema italiani degli anni Cinquanta (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
The contribution deals with the professional knowledge and material cultures that contributed to innovating the infrastructure of Italian cinemas in the early 1950s and the discursive and regulatory driving forces of the modernisation of movie theatres. On the basis of several sources, those aspects are investigated by focusing on the case study of MESAC (later SAM), a technical service company ac- tive since 1946 in the design and renovation of cinema-theatres and based on an engineering culture connected with several industrial and manufacturing districts.